2017
DOI: 10.1155/2017/5271203
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-15 Is a Predictor of Mortality in Critically Ill Patients with Sepsis

Abstract: Growth differentiation factor-15 (GDF-15) is a member of the transforming growth factor-β superfamily related to inflammation and macrophage activation. Serum concentrations of GDF-15 can predict poor survival in chronic diseases, but its role in sepsis is obscure. Therefore, we investigated GDF-15 as a prognostic biomarker in critically ill patients. We measured GDF-15 levels in 219 critically ill patients (146 with sepsis, 73 without sepsis) upon admission to the intensive care unit (ICU), in comparison to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 38 publications
12
49
1
1
Order By: Relevance
“…Using a sandwich ELISA of the same manufacturer, studies have reported median plasma GDF-15 levels of 309 ng/L (IQR 275-411) for healthy individuals and 427 ng/L (IQR 344-626) in obese patients, 18 or median levels of 1097 ng/L and 5753 ng/L for healthy and critically ill patients. 19 Regarding malignant disease, GDF-15 levels were determined with a mean value of 746 ng/L in controls vs 1075 ng/L in colorectal cancer patients. 20 GDF-15 levels within this study correspond well to these data.…”
Section: Gdf-15 Levels In Comparisonsupporting
confidence: 88%
“…Using a sandwich ELISA of the same manufacturer, studies have reported median plasma GDF-15 levels of 309 ng/L (IQR 275-411) for healthy individuals and 427 ng/L (IQR 344-626) in obese patients, 18 or median levels of 1097 ng/L and 5753 ng/L for healthy and critically ill patients. 19 Regarding malignant disease, GDF-15 levels were determined with a mean value of 746 ng/L in controls vs 1075 ng/L in colorectal cancer patients. 20 GDF-15 levels within this study correspond well to these data.…”
Section: Gdf-15 Levels In Comparisonsupporting
confidence: 88%
“…Informed consent was obtained from each participant or their spouse. The patients were categorized as sepsis and non‐sepsis according to the Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis‐3), and were treated following the current guidelines for treatment of sepsis (Surviving Sepsis Campaign) . As a healthy control group, we analyzed blood donors with normal blood counts, normal values of liver enzymes and a negative serology for viral hepatitis and HIV …”
Section: Methodsmentioning
confidence: 99%
“…Growth differentiation factor-15 (GDF-15) is a member of the transforming growth factor β-superfamily and is widely expressed in adult tissues [5]. Elevated GDF-15 levels are associated with chronic inflammation, oxidative stress, and tissue injury [6].…”
Section: Introductionmentioning
confidence: 99%